Charge-entropy-stabilized selenide Ag x Sn1−x Se - Mohamed Oudah; Daisuke Takegami; Shinji Kitao; Jose L. Lado; Anna Meléndez-Sans; Denise S. Christovam; Masato Yoshimura; Ku-Ding Tsuei; Graham McNally; Masahiko Isobe; Kathrin Küster; M. Seto; et al. (Communications Materials)
Abstract Configurational entropy has been discussed for high entropy alloys and high entropy oxides with multiple metal atoms sharing the same atomic site, where the entropy allows for the stability of a single phase material. Typically, the entropy from individual atoms occupying the same site is considered, but here we expand on this to include the entropy coming from charges on the cations sharing the same site. Considering the valence skip nature of Sn, the charge-entropy picture supports the stability region of rocksalt Ag x Sn1−x Se. We find evidence for strong hybridization of the fluctuating Sn state from x-ray photoemission and Mössbauer spectroscopy, where these fluctuations on Sn are maintained to low temperature, well into the superconducting state, due to the lack of long-range order between Ag/Sn atoms in the entropy-stabilized rocksalt structure. Our charge-entropy model expands on the considerations when designing entropy-stabilized materials and opens up the possibility of designing new superconducting materials containing valence-skip elements.